High frequency-link cycloconverters for medium voltage grid connection - Shattock, Nicholas (2014)
As the deployment of renewable generation increases in the worldwide electrical grids, the development of distributed energy storage becomes more and more of an essential requirement. Energy storage devices connected at Medium Voltage allows for much higher powered deployments and this Ph.D. will focus on the power converter used to interface the energy storage device to the electrical grid.